Geospatial analysis of water and nutrient transport in two northern Colorado mixed-landuse watersheds - Cowley, Cortney A., author; Arabi, Mazdak, advisor; Carlson, Ken, advisor; Bledsoe, Brian, committee member; Stromberger, Mary, committee member (Colorado State University. Libraries, 2011)
This study examines the effect of different sources, transport pathways, and hydrologic regimes on phosphorus concentrations along a pristine-urban-agricultural gradient. A total of 48 sampling locations were monitored to characterize total phosphorus concentrations in the Cache la Poudre River Watershed in Northern Colorado. The comprehensive design of sampling locations aimed to capture the influence of anthropogenic activities and geospatial heterogeneity. Samples were collected at seven points in time with distinct climatic and hydrologic characteristics from April 2010 to February 2011. A geographic information system (GIS) was used to measure the overland, irrigation ditch, and stream/river distances from the sources to sampling locations. Analysis of variance, non-linear regression, and multiple linear regression models were used in combination to explore the co-variation of phosphorus concentrations with capacities of upstream WWTPs and CAFOs, along with other geospatial factors. It was evident, under all hydrologic conditions, that phosphorus concentrations downstream from WWTPs were significantly higher than the concentrations upstream of the facilities. Transport from WWTPs governed phosphorus concentrations in surface water during dry and low flow conditions, whereas contribution of CAFOs was significant during rainfall events. The total flow distance (a function of overland, irrigation ditch, and stream/river distances) from CAFOs to the sample locations was strongly associated with phosphorus concentrations during precipitation events. The results of this study provide the foundation for creating a decision support system for water quality analysis, monitoring, and management in the Poudre River basin and other similar mixed-land use watersheds. After examining the Poudre River watershed, a thorough investigation of Boxelder Creek basin was executed. The objectives were to gain an understanding of the geospatial heterogeneity and hydrologic complexity of the watershed using available data, aerial photography, and ground truthing and to develop a model that could accurately simulate the hydrology and nutrient routing in the watershed. Modeling the system using a simplified method for irrigation produced simulated results that were inconsistent with observed flow measurements. These results seem to indicate that irrigation ditches play a vital role in the hydrologic cycle of the basin. Previous studies indicate that watersheds in the study region can be accurately modeled; and although stream flow was not adequately simulated, the model did perform better when estimating total phosphorus concentrations. Therefore, future studies attempting to model basins containing irrigation ditches, like Boxelder Creek basin, should incorporate methods for representing the channels and their various interactions with the natural system. Routing irrigation canals through the watershed, along with irrigation and manure application methods described in this study, should improve the feasibility of modeling the heterogeneity of mixed landuse watersheds.
Keywords: hydrologic regimes; phosphorus; regression; transport pathways; water quality; watershed